2013
DOI: 10.1155/2013/680631
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of High Blood Pressure, Heart Disease, Thalassemia, Sickle-Cell Anemia, and Iron-Deficiency Anemia among the UAE Adolescent Population

Abstract: This study examined the prevalence of high blood pressure, heart disease, and medical diagnoses in relation to blood disorders, among 6,329 adolescent students (age 15 to 18 years) who reside in the United Arab Emirates (UAE). Findings indicated that the overall prevalence of high blood pressure and heart disease was 1.8% and 1.3%, respectively. Overall, the prevalence for thalassemia, sickle-cell anemia, and iron-deficiency anemia was 0.9%, 1.6%, and 5%, respectively. Bivariate analysis revealed statistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…A study conducted in high and low socioeconomic areas of Baghdad province in Iraq found 12·9 % and 17·6 % of male and female adolescents (aged 11-19 years) to be suffering from anaemia (3) . In contrast, a study from the United Arab Emirates reported Fe-deficiency anaemia (IDA) prevalence of 5 % among adolescents (15-18-year-old males and females) (4) . In the Kingdom of Saudi Arabia (KSA), most of the studies on nutritional status have focused on children and adults, hence data on the nutritional status of adolescents are meagre (5,6) Health Directorate in Riyadh city among schoolgirls (16)(17)(18) years old) showed that the prevalence of anaemia was 40·5 % (7) .…”
mentioning
confidence: 93%
“…A study conducted in high and low socioeconomic areas of Baghdad province in Iraq found 12·9 % and 17·6 % of male and female adolescents (aged 11-19 years) to be suffering from anaemia (3) . In contrast, a study from the United Arab Emirates reported Fe-deficiency anaemia (IDA) prevalence of 5 % among adolescents (15-18-year-old males and females) (4) . In the Kingdom of Saudi Arabia (KSA), most of the studies on nutritional status have focused on children and adults, hence data on the nutritional status of adolescents are meagre (5,6) Health Directorate in Riyadh city among schoolgirls (16)(17)(18) years old) showed that the prevalence of anaemia was 40·5 % (7) .…”
mentioning
confidence: 93%
“…The latter has experienced a pronounced economic growth during the last decade and this directly and indirectly influenced the lifestyle of Emirati population and led to a considerable increase in the prevalence of several risk factors for chronic disorders such as DM [3]. In 2009, Diabetes International Foundation revealed that five of the gulf countries are among the top ten countries for prevalence of DM with an estimated increase of 93.9% between 2010 and 2030 [1].…”
Section: Introductionmentioning
confidence: 99%
“…The mean age of the study sample was 16 years (standard deviation 1.22). Detailed information in relation to the number of schools sampled and response rates has been published elsewhere (20).…”
Section: Resultsmentioning
confidence: 99%